Radiation emitted from patients undergoing nuclear medicine examination at Udonthani Cancer Hospital - Wisetnan, Chaisunthorn; Awikunprasert, Panatsada; Kaewsombat, Thayada; Molee, Patamaporn (Journal of Associated Medical Sciences, 2021)
Background: Diagnostic nuclear medicine involves intravenous injection of radiopharmaceutical substances into the patient, after which they still possess the substance within their bodies and depict mobile radiation sources. Although the amount of radiation emitted is little and harmless to others, practitioners in and outside the Division of Nuclear Medicine along with related personnel and relatives of the patient are anxious about radiation exposure from a patient undergoing nuclear medicine examination. Objectives: This study aimed to measure radiation doses from the patients at different times and distances. Materials and methods: The radiation dose was measured from 66 patients (19-79 years) undergoing bone scan, MUGA scan, and thyroid scan. The data were collected at different times intervals and different distances from the patients. Results: The results showed that the radiation dose from patients after a bone scan and MUGA scan at a distance less than 0.50 meter was higher than 10 μSv/hr, which is the radiation exposure limit of the practitioner. Conclusion: Results of this study are helpful in operation planning such as increasing the distance and reducing the time of close contact, which can ease anxiety of concerned personnel, while radiation practitioner training as well as educating patients and relatives must be carried out to encourage better understanding.